The Influence of Product Quality, Brand Trust and Price Perception on Brand Loyalty through Brand Image as a Mediating Variable on Ventela Brand Sneakers (A Study on Consumers of Ventela Surabaya Official Store) - Siahaan, Wina Monalisa; Susanti, Ety Dwi (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2024)
The aim of this study is to analyze the influence of product quality, brand trust, and price perception on brand loyalty in Ventela Sneaker Brand. This is done by considering the role of brand image as a mediator, in a study involving consumers from Ventela Surabaya Official Store. The sampling method used is accidental sampling involving 100 respondents. Data analysis is conducted using PLS analysis with the assistance of the SmartPLS program. The results of this study indicate that product quality and brand trust significantly influence brand image. Price perception does not have a significant influence on brand image. Product quality, price perception, and brand image significantly influence brand loyalty. However, brand trust does not significantly influence brand loyalty. Product quality and brand trust through brand image significantly influence brand loyalty. Meanwhile, price perception does not have a significant influence on brand loyalty.